Concerti musicali, Op. 6 - Mangsen, Sandra (Oxford University Press, Oxford, 2005)
RESUMEN: Autor Giuseppe Torelli, ed. John G. Suess. Recent Researches in the Music of the Baroque Era, 115. (A-R Editions, Middleton, Wis., 2002)